EVOLUTION OF OFFICIAL LANGUAGE IN KOREA - OH, Kyong-geun (Comparative Legilinguistics, 2016)
Chinese characters and Buddhist books reached Korea about third century of the Common Era. From that moment Korea became the official part of the Chinese culture and civilization (Cheon So-yeong 2007, 362). Despite the fact that ideographic Chinese characters were not fit for the Korean language, Koreans, having no writing system of their own, adopted the script. Chinese characters became the basis for the Korean writings and official documents till mid-19thcentury. Initially, texts were formulated in Chinese. The sentence order typical of the Chinese language was used in them too. At the same time Koreans read out such texts adapting the pronunciation of Chinese characters to the rules of Korean phonetics. With the flow of time, new styles of writing started emerging including gugyeol and idu. Gugyeol was a style in which the sentence word order was still typical of the Chinese language. It was, however, enriched with Korean grammatical morphemes which were absent in Chinese but were vital for Korean. The next stage in the development of Korean writings is called idu. What is typical of idu is the fact that the sentence word order changed into typical of Korean spoken language (e.g. the verb was transferred at the end of the sentence). None of the methods was fully efficient. Therefore, the most significant breakthrough was the invention of the Korean alphabet called hangeul by the king Sejong.